PTU-178 Clinical Utility Of Endofaster® In Patients On Chronic Ppi Therapy Undergoing Upper Gi Endoscopy. (9th June 2014) - Cayado-Lopez, R; Bornschein, J; Zeki, S; Udarbe, M; Di Pietro, M
Abstract : Introduction: Patients undergoing upper GI endoscopy (OGD) are often on chronic PPI therapy for dyspeptic symptoms or gastro-oesophageal reflux disease (GORD). Continued PPI therapy at the time of the endoscopy can influence the outcome of H. pylori testing via rapid urease test (CLO) or even histology. In addition, complete response to PPI in patient with GORD and/or Barrett's oesophagus (BO) is often not fully predicted by the clinical history. We hypothesised that rapid testing of H. pylori status and gastric pH by Endofaster® could provide the physician with real-time information useful to influence patient management. Methods: This pilot feasibility study included 135 consecutive patients at a single centre who underwent OGD for BO surveillance/endotherapy (n = 95), screening for hereditary diffuse gastric cancer (n = 11) and evaluation of GORD/dyspepsia (n = 29). The pH and the H.pylori status were measured on 4 mL of gastric aspirate using the Endofaster®, which connects to the suction port of the gastroscope. If clinically indicated, CLO test or gastric biopsies were performed. Endofaster® results were matched with the history of PPI intake (PPI type and time of last dose) and results of CLO and gastric histology. Results: Overall, 109 patients were on chronic PPI treatment and of these 74% presented with gastric hypochloridia (pH >4) at Endofaster® analysis. Forty-nine patients reported PPI intake on the same day of the OGD and 15% of these (n = 7) had acid gastric pH (<4). Fifty-nine patients had CLO test and 57 had gastric histology results available, while 26 patients had both. Only 1 patient was positive for H. pylori on histology, which was also positive at Endofaster®. Two patients had a positive CLO test, of which one was Endofaster® positive for H. pylori. Eleven patients were positive at the Endofaster® but not at CLO, of which 91% were on chronic PPI (n = 10). Conclusion: This feasibility study shows that a significant proportion of patients on chronic PPI therapy still have acidic gastric pH suggesting sub-optimal response to PPI. Endofaster® may detect H.pylori infection in patients on chronic PPI therapy, which are often false negatives when tested by CLO and histology. A prospective study matching Endofaster® data with gold standard tests for H. pylori status and gastro-esophageal reflux are needed to conclude on the clinical implications of these findings. Disclosure of Interest: None Declared.